PENINGKATAN KEAKTIFAN DAN MOTIVASI BELAJAR BIOLOGI MELALUI DISCOVERY LEARNING PADA SISWA KELAS XI IPA ICT 2 SMA MUHAMMADIYAH 1 KARANGANYAR TAHUN PELAJARAN 2014/2015 - Yulaeka Mawar Dani; Maridi Maridi; Bowo Sugiharto (BIO-PEDAGOGI, 2016)
The objective of this research is to improve student’s activity and motivation of class XI IPA ICT 2 SMA Muhammadiyah 1 Karanganyar academic year 2014/2015. The result of the observation which is student appeared unenthusiastic attitude towards learning is being implemented, so its needed a learning model which accommodate student’s activity and motivation learning. One of the models that accommodate and treat student’s activity and motivation learning less is discovery learning model. Kind of this research is classroom action research.The methods of data collection are through observation, questionnaire, and interviews. The data are in the form of students’ activity and motivation at every phase of discovery learning models in each cycle of the action. The analysis of the quality of percentace average observation and questionnaire of student’s activity and motivation learning. The results of the application of discovery learning model showed an increase of the quality of student’s activity and motivation. The observation quality student’s activity in the pre cycle is 38,82%, the first cycle is 66,76%, and the second cycle is 83,71%. The questionnaire quality student’s activity in the pre cycle is 51,12%, the first cycle is 75,13%, and the second cycle is 78,68%. The observation quality student’s motivation in the pre cycle is 42,86%, the first cycle is 67,30%, and the second cycle is 79,89%. The questionnaire quality student’s motivation in the pre cycle is 49,29%, the first cycle is 71,86%, and the second cycle is 76,55%.Based on the result of the research, it can conclude that the application of discovery learning model can improve student’s activity and motivation learning. Keywords: Activity, Motivation, Discovery Learning